Co‐occurrence of late potential and discrete prepotential on ablation site in a case of cardiac crux located premature ventricular complexes successfully ablated within the middle cardiac vein. Issue 3 (15th May 2019) - Gulsen, Kamil; Bayrak, Fatih; Akdemir, Baris; Polat, Veli; Barman, Hasan Ali; Ince, Orhan; Okuyan, Ertugrul
Abstract: Some premature ventricular complexes (PVCs) originate from the coronary venous system. The great cardiac vein and the anterior cardiac vein are the most frequent localizations. The middle cardiac vein is an unusual anatomy for a point of origin for PVC. We present here a case of frequent PVCs with characteristic electrocardiographic features, which we successfully ablated inside the middle cardiac vein.